Revisiting causalities of economic and non-economic factors on oil prices in major oil-exporting countries: a novel approach - Bildirici, Melike E.; Erdogan, Levent (TAYLOR & FRANCIS INC, 2025)
The global oil markets have experienced substantial fluctuations or collapses in oil prices due to the global financial crisis as well as recent shocks and geopolitical events. The source of oil price fluctuations has been analyzed in many papers, but these papers did not examine simultaneously the relation between oil prices, economic and non-economic variables. The purpose of study is to fill the research gap by delving into the presence of nonlinear relationship and causality between economic variables, non-economic variables and crude oil prices in 10 major oil-producing countries. We apply panel logistic transition-VAR (PLSTRVAR) and PLSTRVAR Granger Causality methodologies covering the data from 1997:1 to 2024:6 in the light of the structural breakage, regime shifts and business cycle. The empirical findings provide following results. Firstly, the PLSTRVAR method confirms significant relationship between economic variables, non-economic variables and oil prices. Secondly, the PLSTRVAR Granger Causality method confirms that infectious disease, global economic policy uncertainty and geopolitical risks are Granger cause of oil prices in both regimes. In addition, for both regimes, the estimation results support that while the causality is directed from infectious disease and geopolitical risks to oil prices, bidirectional causality also arises between global economic policy uncertainty and oil prices. The results also provide evidence of unidirectional causality from oil prices to inflation in both regimes, from oil prices to real exchange rate in regime 2 and bidirectional causality between real exchange rate and oil prices in regime 1. Thirdly, the results show that not only non-economic variables have mutual effect each other but also have significant effect on economic variables. Lastly, the use of standard panel VAR and panel Granger causality results mostly can lead to infer wrong policy recommendations since it ignores the variables with structural breakage and business cycle. Overall results suggest that policy-makers should consider the flexibility, transparency, global cooperation, and long-term planning are key principles to navigate the challenges posed by these factors and also to maintain the stability of the energy market and sustainable economic growth.
Keywords: Exchange rate; geopolitical risks; global economic policy uncertainty; inflation; non-linear panel VAR method; PLSTVAR method; oil prices; EXCHANGE-RATE; US DOLLAR; NONLINEAR RELATIONSHIP; CO2 EMISSIONS; PANEL-DATA; POLICY; TESTS; RATES; COINTEGRATION; ENERGY; Energy & Fuels